Eksistensi Kain Tenun Tembe Nggoli bagi Masyarakat Suku Mbojo dalam Bidang Sosial dan Ekonomi - Fahrur Rozi; Muhammad Shulhan Hadi; Suhupawati Suhupawati; B. Fitri Rahmawati (Universitas Hamzanwadi, 2024)
This study analyzes the social and economic roles and continued existence of Tembe Nggoli woven cloth among the Mbojo community in Sangia Village, Sape District, Bima Regency. A qualitative descriptive approach was employed. Data were collected through field observations, structured and unstructured interviews, and documentation. Informants included community elders, senior and active women weavers, and village officials. Data were analyzed through data condensation, data display, conclusion drawing, and verification. The findings show that Tembe Nggoli has a dual position as cultural heritage and a source of livelihood. Socially, it functions as a marker of Mbojo identity, a symbol of honor, a medium for transmitting values, and an important element in customary ceremonies, weddings, religious activities, and the Rimpu dressing tradition. Social change has broadened its use from selected social groups to the wider community and contemporary fashion, although this democratization has reduced part of its former sacred character. Economically, weaving provides primary or supplementary income for women, supports household needs and children's education, and creates opportunities in the creative economy and cultural tourism. The continuity of Tembe Nggoli is constrained by weak intergenerational regeneration, lengthy production, limited marketing capacity, and competition from modern textiles. Strengthening weavers' organizations, innovating products without separating motifs from their cultural meanings, documenting local knowledge, utilizing natural dyes, and expanding digital marketing are therefore essential to connect cultural preservation with sustainable community welfare.